ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP PEMBELIAAN BUAH JERUK IMPOR DAN LOKAL SELAMA PANDEMI COVID-19 DI SUPERMARKET BRASTAGI - Saragi, Cyprianus P.H; Sitohang, Maryanti (Jurnal Manajemen dan Bisnis, 2023)
This research aims to determine the relationship between the quality of imported and local citrus fruit products and the level of consumer satisfaction during the Covid-19 pandemic, and to determine the attributes of imported and local citrus fruits based on the level of consumer satisfaction during the COVID-19 pandemic in the research area. Determination of the research area was carried out purposively (intentionally). The data analysis method used is descriptive analysis, Pearson correlation analysis, and fishbein multi-attribute analysis. The results showed that the product attributes of imported and local citrus fruits in terms of taste, size level, color, price level, water content, and fruit origin had a positive relationship to consumer satisfaction during the Covid-19 pandemic. The quality that has no positive relationship to consumer satisfaction is the seed content. The order of the attributes that consumers compare in purchasing imported and local oranges during the Covid-19 pandemic is the freshness attribute (23.57%) for imported and local oranges (22.99%).